The search for an ideal : six Canadian intellectuals and their convictions in an age of transition, 1890-1930 - Shortt, S. E. D. (Samuel Edward Dole), 1947- (Heritage., 1976)
Within the context of the debate between idealism and empiricism, this book studies the ideas of six representative Canadian intellectuals of the late Victorian era. These six were chosen primarily because of their ideas on contemporary social questions.